Enhancing Teaching Computational Thinking: a Systematic Mapping of Pedagogical Patterns - Atieno, Loice Victorine; Turcsanyi Szabo, Marta (Journal of Education, Technology and Computer Science, 2022)
Efforts to enhance understanding Computational thinking (CT) are curtailed by: (i) problem solving complexity linked to implementing a new subject; and (ii) teaching CT for problem solving is a new field. Unfortunately, the only support available are pedagogic theories and anecdotal explaining other’s practice. Implementing these theories can be challenging, hence continuous research on realistic methods of sharing successful and commendable practice amongst educators, necessitating this study. Systematic Mapping (SM) was used with the following steps: research questions formulation; identifying keywords; identifying source databases; defining inclusion and exclusion criteria; constructing the search string; conduct the search; data extraction; and presentation of results. 22 studies were selected with the majority being solution proposal research. The identified pedagogical patterns were mapped to the 5Es of Framework of Action. Several patterns for solving assessment related problems were also identified hence the inclusion of the 6th E (Evaluation).